PROPOSIÇÃO E VALIDAÇÃO DE UMA ESCALA DE AVALIAÇÃO DO COMPORTAMENTO DE DESCARTE DE LIXO ELETROELETRÔNICO (ADMPG Journal, 2021)
This article aims to create a scale to assess the behavior of electronic waste disposal by consumers in general. Data collection took place through an electronic questionnaire, via Google Docs, disclosed on the researchers' social networks. The questionnaire was structured with 8 questions about the profile of respondents, 5 questions about knowledge and habits of electronic waste disposal and 11 questions from the electronic waste disposal behavior assessment scale. The total sample consisted of 128 participants. To check the validity of the scale, Exploratory Factor Analysis and Cronbach's Alpha coefficient were used as a way to estimate the reliability of the scale. From the Factor Analysis, 3 factors were found that brought together 8 variables, out of 11 in the original scale. These factors were called correct disposal behavior, incorrect disposal behavior and behavior of storing garbage at home. All factors obtained consistent indicators, which demonstrate the validity of the model to assess people's behavior in relation to e-waste disposal.